Appropriate reference gene selection for real-time PCR data normalization during rat mesenchymal stem cell differentiation - Farrokhi, A.; Eslaminejad, M. B.; Nazarian, H.; Moradmand, A.; Samadian, A.; Akhlaghi, A. (Cellular and Molecular Biology, 2012)
Reverse transcription quantitative PCR (RT-qPCR) is one of the best methods for the study of mesenchymal stem cell (MSC) differentiation by gene expression analysis. This technique needs appropriate reference or housekeeping genes (HKGs) to normalize the expression of the genes of interest. In the present study the expression stability of six widely used HKGs including Actb, Btub, Hprt, B2m, Gusb and Tfrc was investigated during rat MSC differentiation into osteocytes, adipocytes and chondrocytes lineages using geNorm and NormFinder software. RT-qPCR data analyzed by geNorm revealed the different sets of suitable reference genes for each cell type. NormFinder also showed similar results. Analysis of the combined data of MSCs with each differentiated cell type revealed the considerable shift in expression of some reference genes during differentiation; for example Gusb and B2m were among the least stable genes in MSCs but the most stable in chondrocytes. Normalization of specific genes for each lineage by different reference genes showed considerable difference in their expression fold change. In conclusion, for the appropriate analysis of gene expression during rat MSC differentiation and also for monitoring differentiation procedures, it is better to consider precisely the reference gene stability and select suitable reference genes for each purpose.